PENGARUH BAURAN PEMASARAN TERHADAP NIAT BERLANGGANAN KEMBALI PADA HARIAN UMUM TIMOR EXPRESS DI KOTA KUPANG - Markus Agustinus Foes; Antonio E.L. Nyoko; Paulina Y. Amtiran (Universitas Nusa Cendana, 2018)
This study aims to analyze the influence of the Marketing Mix (Product, Price, Distribution andPromotion) on the Reguler Repurchase Intention. The method used in this study is a quantitativemethod that was done through data collection, interpretation of data and conclusion of results. Datacollection technique in this study is questionnaires with respondents as many as 70 people who arereguler customers of Daily Timor Express Kupang. This research uses Multiple Linear RegressionAnalysis. The result shows that the Product has a positive and insignificant effect on the RegulerRepurchase Intention, the Price has a positive and significant influence on the Reguler RepurchaseIntention, the Distribution has a positive and insignificant influence on the Reguler RepurchaseIntention, while the the Promotion has a positive and insignificant influence on the RegulerRepurchase Intention. The simultaneous test results in this study revealed that all Marketing Mixvariables affect the Reguler Repurchase Intention.Keyword : Reguler Repurchase Intention, Pricing, Product, Distribution Promotion, MarketingMix